2015
DOI: 10.1073/pnas.1418198112
|View full text |Cite
|
Sign up to set email alerts
|

Superficial white matter fiber systems impede detection of long-range cortical connections in diffusion MR tractography

Abstract: In vivo tractography based on diffusion magnetic resonance imaging (dMRI) has opened new doors to study structure-function relationships in the human brain. Initially developed to map the trajectory of major white matter tracts, dMRI is used increasingly to infer long-range anatomical connections of the cortex. Because axonal projections originate and terminate in the gray matter but travel mainly through the deep white matter, the success of tractography hinges on the capacity to follow fibers across this tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
412
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 410 publications
(428 citation statements)
references
References 57 publications
15
412
0
1
Order By: Relevance
“…In addition, tractography may be challenging in the brain regions of high fiber complexity (for a more detailed discussion, see Jbabdi and Johansen-Berg, 2011). For example, it has been suggested that tracking white matter fibers into the cortex to find their exact termination may be further limited by the complexity added by local corticocortical connections passing parallel to the cortex (Reveley et al, 2015). Taking into account these limitations, recent studies have shown that probabilistic tractography, which greatly capitalizes on the quantitative potential of assessing the probability of a connection between the two regions, can be applied successfully in both human and nonhuman primate species to draw conclusions not only about the nonhuman primate brain in a validated model but also the human brain and how it may differ from that of the nonhuman primate.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, tractography may be challenging in the brain regions of high fiber complexity (for a more detailed discussion, see Jbabdi and Johansen-Berg, 2011). For example, it has been suggested that tracking white matter fibers into the cortex to find their exact termination may be further limited by the complexity added by local corticocortical connections passing parallel to the cortex (Reveley et al, 2015). Taking into account these limitations, recent studies have shown that probabilistic tractography, which greatly capitalizes on the quantitative potential of assessing the probability of a connection between the two regions, can be applied successfully in both human and nonhuman primate species to draw conclusions not only about the nonhuman primate brain in a validated model but also the human brain and how it may differ from that of the nonhuman primate.…”
Section: Resultsmentioning
confidence: 99%
“…S1). The perfusion-fixation protocol, and other preparations for data acquisition and scanning of the ex-vivo brain are described in detail in the previous study (Reveley et al, 2015) Creation of 3D digital atlas template from 2D atlas…”
Section: Creation Of An Ex-vivo Surrogate Anatomical Volumementioning
confidence: 99%
“…For example, diffusion MRI provides the means to track white matter pathways (Fig. 4) and has been used to identify white matter connectivity disruptions associated with cognitive disorders such as dyslexia 77 ; however, diffusion imaging has inherent biases that limit its ability to accurately track connections across the entire brain 78,79 . The last decade has seen a proliferation of approaches to model functional connectivity on the basis of functional MRI data, though the dust has yet to settle regarding which methods are most effective (for example, ref.…”
Section: Connectomicsmentioning
confidence: 99%